Pengaruh Implementasi Pelatihan Coaching (Bimbingan) Kepala Ruang Terhadap Kinerja Perawat Pelaksana Di RS X Tangerang - Mey Lys Ceryah Hutasoit; Asnet Leo Bunga; Havidz Aima; Dewi Anggraeni (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
The development of nursing education in Indonesia is not yet in line with improving the quality of nurse performance. One of the efforts to improve the performance of nurses through the implementation of coaching training is given by the supervisor to the implementing nurses The purpose of this study was to see the effect of the implementation of supervisor coaching training on the performance of the implementing nurses at the X Hospital in Tangerang. This research method uses quasi-experimental quantitative method, non randomized control group design pre test and post test. The research sample consisted of 101 nurses and 8 supervisor consisting of 5 supervisor , 76 nurses implementing the intervention group, 3 supervisor and 25 nurses implementing the control group. The results showed that there was an increase in the skills of supervisor by 4% with a mean post test skill of 82%. The implementation of supervisor coaching training has an effect on increasing the performance of the nurse nurses by 4.2% statistically significant with (p = 0.000). The implementation of supervisor coaching were statistically significant (p = 0,000) to the performance of the implementing supervisor, gender was significant (p = 0.009). For the supervisor coaching variable, age, education and duration of work did not affect the performance snurse. Therefore, effort needs to be applied to achieve nurses’ quality performance and coaching technique implementation could become a sustainable recommendation that significantly proved in developing nurse performance.